2017
DOI: 10.1007/s00431-017-2975-z
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli early-onset sepsis: trends over two decades

Abstract: There is an urgent need to reconsider the empirical therapy used in neonatal EOS, particularly in VLBW newborns. What is Known: • E. coli early-onset sepsis (EOS) and E. coli resistant strains have been described as overall stable but increasing in VLBW neonates (< 1.500 g) in previous studies. What is New: • Our study shows an increasing incidence of E. coli EOS in all age groups, overruling group B Streptoccocus for the last 10 years. E. coli resistant strains also increased equally in all age groups, with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 28 publications
1
40
0
3
Order By: Relevance
“…They reported ampicillin resistance in 75% of isolates and gentamicin resistance in 12% overall, with considerable increase in resistance reported in the period 2010–2014. Cefotaxime resistance, however, was rarely found . In our nationwide study, we demonstrated significant gentamicin resistance among Gram‐negative isolates in general (16%) and specifically among Escherichia coli and Klebsiella isolates (17%).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…They reported ampicillin resistance in 75% of isolates and gentamicin resistance in 12% overall, with considerable increase in resistance reported in the period 2010–2014. Cefotaxime resistance, however, was rarely found . In our nationwide study, we demonstrated significant gentamicin resistance among Gram‐negative isolates in general (16%) and specifically among Escherichia coli and Klebsiella isolates (17%).…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies demonstrated low gentamicin resistance in Gram‐negative isolates, 2% in Australia and New Zealand and 0–4% in studies from the United States, leading to the conclusion that ampicillin plus gentamicin remains appropriate empiric regimen for EOS . However, an alarming increase in the antimicrobial resistance rates of Gram‐negative bacteria in neonates, including cefotaxime resistance as ESBL phenotype, and gentamicin resistance, has been reported in India and other countries . Indeed, a recent publication from Spain evaluated trends in clinical and microbiologic characteristics of Escherichia coli EOS in 1994–2014 in a single centre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among febrile infants≤28 days-old, the prevalence of bacteremia and meningitis is high, E.coli is one of the most common bacterial pathogens [9] . The incidence of E. coli early-onset sepsis in very low birth weight infants was 10.4 cases per 1000 live births and mortality reached 35.3% [10] . A recent meta-analysis based on a systematic review of the published studies in Chinese literature demonstrates that in newborn infants hospitalized in Chinese NICUs, roughly 50% of all E. coli bloodstream isolates (regardless of early onset or late onset) are multi-drug resistant due to extended-spectrum beta-lactamase (ESBL) production [11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in the incidence of early-onset Escherichia coli sepsis has occurred during the same time period (4). Several studies have found that the incidence of early-onset E. coli sepsis has continued to increase over the last decades, and this has manifested itself as increased disease severity and risk of newborn death (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%